ANALISIS NILAI PENDIDIKAN KARAKTER DALAM CERITA RAKYAT SELUMA - Esma Junaini; Emi Agustina; Amril Canrhas (Universitas Bengkulu, 2017)
This study aims to describe the value of character education contained in seluma folklore. This research data is folklore obtained from the recording and written documentation.in this research used descriptive analysis method. Data collection techniques used are recoding technique record. The result showed that the values of character education contained in the folklore of seluma is very good to form human character from an early age. The value of character education contained in seluma folklore is the value of education that is very close to everyday life so it is suitable to implanted in self. In seluma folklore especially in fairy tales and legends of character education values contained in fairy tales and legends that is, the value of courage, mutual need, self-discipline, self-respect, faimess, caring, protecting each other, and respect others, the attitude of deliberation, and the attitude of cooperation.